Bioelectrode composition, bioelectrode, and method for producing bioelectrode
The bioelectrode composition, featuring specific salts and particles, addresses conductivity and biocompatibility issues, enabling rapid signal detection and residue-free operation, suitable for medical wearables.
Patent Information
- Application Number
- JP2021199758
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-06
- Filing Date
- 2021-12-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-12-09
AI Technical Summary
Existing bioelectrodes face challenges in maintaining conductivity and biocompatibility over long-term use, causing skin allergies and residue, and require improvements in signal detection immediacy.
A bioelectrode composition using a polymer with ammonium, sodium, or silver salts of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide, combined with silica, alumina, or zirconia particles, and a silicone compound with a polyglycerin structure, to form a biocontact layer that is conductive, residue-free, and quickly responsive.
The bioelectrode composition ensures excellent conductivity and biocompatibility, allowing for rapid signal collection without skin residue, even when wet or dry, and is lightweight with a transparent design.
Smart Images

Figure 0007611807000124 
Figure 0007611807000125 
Figure 0007611807000126
Abstract
Description
[Technical field]
[0001] The present invention relates to a bioelectrode that can be brought into contact with the skin of a living body and detect a bodily condition such as heart rate by an electrical signal from the skin, a method for producing the same, and a bioelectrode composition that is suitably used for the bioelectrode. [Background technology]
[0002] In recent years, the development of wearable devices has progressed with the spread of IoT (Internet of Things). Typical examples are watches and glasses that can connect to the Internet. In addition, wearable devices that can constantly monitor the condition of the body are needed in the medical and sports fields, and these are expected to be growth fields in the future.
[0003] In the medical field, wearable devices that monitor the state of the body's organs by sensing weak currents, such as in electrocardiograms, which detect the movement of the heart through electrical signals, are being considered. In electrocardiograms, electrodes coated with conductive paste are attached to the body to perform the measurement, but this is a one-time, short-term measurement. In contrast, the aim of developing medical wearable devices such as those mentioned above is to develop devices that constantly monitor health conditions for several weeks in a row. Therefore, bioelectrodes used in medical wearable devices are required to have no change in conductivity even when used for long periods of time and to be free of skin allergies. In addition to these, they are also required to be lightweight and to be able to be manufactured at low cost.
[0004] Wearable medical devices include those that are attached to the body and those that are incorporated into clothing. As a type that is attached to the body, a bioelectrode that uses a water-soluble gel containing water and electrolytes, which are the materials for the conductive paste mentioned above, has been proposed (Patent Document 1). The water-soluble gel contains sodium, potassium, and calcium as electrolytes in a water-soluble polymer that holds water, and converts changes in ion concentration from the skin into electricity. On the other hand, as a type that is incorporated into clothing, a method has been proposed in which a conductive polymer such as PEDOT-PSS (Poly-3,4-ethylenedioxythiophene-Polystyrenesulfonate) or cloth with silver paste incorporated into the fibers is used as an electrode (Patent Document 2).
[0005] However, when using the above-mentioned water-soluble gel containing water and electrolytes, there is a problem that the conductivity is lost when the water dries out. On the other hand, when using metals with a high ionization tendency such as copper, there is a problem that some people may develop skin allergies, and when using conductive polymers such as PEDOT-PSS, there is a problem that the conductive polymer is highly acidic and therefore may develop skin allergies, and the conductive polymer may peel off from the fibers during washing.
[0006] In addition, because of their excellent electrical conductivity, the use of metal nanowires, carbon black, carbon nanotubes, and the like as electrode materials has also been considered (Patent Documents 3, 4, 5). Metal nanowires have a high probability of contact between wires, so they can conduct electricity with a small amount of additive. However, metal nanowires are thin materials with sharp tips, which can cause skin allergies. Carbon nanotubes are also irritating to living organisms for the same reason. Although carbon black is not as toxic as carbon nanotubes, it is somewhat irritating to the skin. Thus, even if the material itself does not cause an allergic reaction, the shape and irritability of the material can deteriorate biocompatibility, making it difficult to achieve both electrical conductivity and biocompatibility.
[0007] Metal films are highly conductive and one would think they would function as excellent bioelectrodes, but this is not necessarily the case. When the heart beats, not only a weak current is released from the skin, but also sodium ions, potassium ions, and calcium ions. For this reason, it is necessary to convert the change in ion concentration into an electric current, but precious metals, which are difficult to ionize, are inefficient at converting ions from the skin into an electric current. Therefore, bioelectrodes using precious metals have a high impedance, and there is a high resistance to electrical current passing through the skin.
[0008] A lithium ion conductive composite for solid electrolytes has been proposed, which uses a silicon-atom-containing compound having a segment containing lithium ions. It is known that the composite has good electrical conductivity and good lithium ion transport number at the temperature at which the battery is used, as well as excellent mechanical properties, moldability, and good adhesion to the electrodes, and therefore results in a highly safe battery with reduced or eliminated risks such as fire and leakage (Patent Document 6).
[0009] Bioelectrodes with added ionic polymers have been proposed (Patent Documents 7, 8, 9). Bioelectrodes made by adding ionic polymers and carbon powder to a silicone adhesive have adhesive properties and are highly water repellent, so they can stably collect biosignals even when attached to the skin for long periods of time while showering or sweating. Ionic polymers do not pass through the skin, so they are not irritating to the skin and are highly biocompatible, which also makes it possible to wear the bioelectrode for long periods of time.
[0010] Silicone is an insulator by nature, but the combination of ionic polymer and carbon powder improves its ionic conductivity, allowing it to function as a bioelectrode. However, there is a demand for further improvement in performance through improved ionic conductivity.
[0011] The aforementioned Patent Documents 7, 8, and 9 show that additives of silicone compounds having polyether chains are effective in improving ionic conductivity. Polyether chains are also used to improve the ionic conductivity of lithium ion polymer batteries, and are effective in improving ionic conductivity. However, the ionic conductivity of the water-soluble gel is lower than that of the hydrous gel, and further improvement of the ionic conductivity is necessary.
[0012] Bioelectrodes need to be able to pick up signals immediately after being attached to the skin. With gel electrodes, the ion concentrations of the skin and the electrode are similar, allowing ions to move in and out smoothly, and the speed at which ions move through the hydrous gel is fast, making it possible to detect signals immediately after being attached to the skin. On the other hand, with dry electrodes, it takes a long time for a signal to be detected after being attached to the skin. This is thought to be because a signal is not produced until the ions released from the skin are saturated on the surface of the dry electrode.
[0013] As described above, bioelectrodes need to be able to obtain signals immediately after application to the skin, but the development of dry electrodes has presented many problems. Therefore, there is a demand for the development of bioelectrodes that do not leave residue or cause skin irritation and can obtain signals immediately after application to the skin. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] International Publication No. 2013 / 039151 [Patent Document 2] JP 2015-100673 A [Patent Document 3] Japanese Patent Application Publication No. 05-095924 [Patent Document 4] JP 2003-225217 A [Patent Document 5] JP 2015-019806 A [Patent Document 6] JP 2007-059092 A [Patent Document 7] JP 2018-099504 A [Patent Document 8] JP 2018-126496 A [Patent Document 9] JP 2018-130533 A Summary of the Invention [Problem to be solved by the invention]
[0015] The present invention has been made to solve the above problems, and aims to provide a bioelectrode composition that can be attached to the skin to quickly collect signals and form a biocontact layer for a bioelectrode that does not leave any residue on the skin, a bioelectrode in which a biocontact layer is formed from the bioelectrode composition, and a method for manufacturing the same. [Means for solving the problem]
[0016] In order to solve the above problems, the present invention provides the following bioelectrode composition, bioelectrode, and method for producing the same.
[0017] In the present invention, a polymer compound (A) containing a repeating unit a having a structure selected from the group consisting of an ammonium salt, a sodium salt, a potassium salt, and a silver salt of any one of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide; one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles; and a bioelectrode composition comprising:
[0018] Such a bioelectrode composition can be applied to the skin to rapidly collect signals and can form a biocontact layer for a bioelectrode that does not leave any residue on the skin.
[0019] The repeating unit a preferably has a structure represented by any one of the following general formulas (1)-1 to (1)-4. [ka] (In the general formula (1)-1, Rf1 and Rf2 are a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group. When Rf1 and Rf2 are oxygen atoms, Rf1 and Rf2 are one oxygen atom bonding to one carbon atom to form a carbonyl group, Rf3 and Rf4 are a hydrogen atom, a fluorine atom, or a trifluoromethyl group, and at least one of Rf1 to Rf4 is a fluorine atom or a trifluoromethyl group. In the general formulas (1)-2, (1)-3, and (1)-4, Rf5, Rf6, and Rf7 are each a fluorine atom, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom. In the general formulas (1)-1 to (1)-4, M + is an ion selected from an ammonium ion, a sodium ion, a potassium ion, and a silver ion. In the general formula (1)-2, m is an integer of 1 to 4.
[0020] When the repeating unit a has such a structure, it is possible to obtain a bioelectrode composition capable of forming a biocontact layer for a bioelectrode having superior electrical conductivity and biocompatibility.
[0021] It is more preferable that the repeating unit a has at least one type selected from the repeating units a1 to a7 represented by the following general formula (2). [ka] (In general formula (2), R 1 , R 3 , R 5 , R 8 , R 10 , R 11 , and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 , and R 14R are each independently a single bond or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms. The hydrocarbon group may have an ester group, an ether group, or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 In the formula, one or two of the hydrogen atoms may be substituted with a fluorine atom. Each of X1, X2, X3, X4, X6, and X7 is independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, and X5 is a single bond, an ether group, or an ester group. Y is an oxygen atom or -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 may form a ring together with Rf1' and Rf5' are a fluorine atom, a trifluoromethyl group, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6, and a7 are each 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0≦a7≦1.0, <a1+a2+a3+a4+a5+a6+a7≦1.0である。M + is an ion selected from ammonium ion, sodium ion, potassium ion, and silver ion.
[0022] If the repeating unit a has such a structure, it is possible to obtain a bioelectrode composition capable of forming a biocontact layer for a bioelectrode having even better electrical conductivity and biocompatibility.
[0023] The polymer compound (A) preferably contains an ammonium ion represented by the following general formula (3) as the ammonium ion constituting the ammonium salt. [ka] (In general formula (3), R 101d , R 101e, R 101f and R 101g R is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 14 carbon atoms, a linear, branched, or cyclic alkenyl group or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more groups selected from an ether group, a carbonyl group, an ester group, a hydroxy group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d and R 101e , or R 101d , R 101e and R 101f may form a ring together with the nitrogen atom to which they are attached, and when they form a ring, R 101d and R 101e , or R 101d , R 101e and R 101f is an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having the nitrogen atom in the general formula (3) in the ring.
[0024] If the composition contains such a polymer compound (A) containing ammonium ions, it can be used as a bioelectrode composition capable of forming a biocontact layer for a bioelectrode having even better electrical conductivity and biocompatibility.
[0025] Furthermore, it is preferable that the composition contains a compound (C) having a polyglycerin structure.
[0026] A bioelectrode composition containing the compound (C) having a polyglycerin structure can form a biocontact layer for a bioelectrode that can be attached to the skin and rapidly collect signals.
[0027] The compound (C) having a polyglycerin structure is preferably a silicone compound having a polyglycerin structure.
[0028] A bioelectrode composition containing a silicone compound having a polyglycerin structure can form a biocontact layer for a bioelectrode that can be attached to the skin and quickly collect signals.
[0029] The silicone compound having a polyglycerin structure is preferably represented by either of the following general formulas (4) and (5). [ka] (In the formula, R 1 are each independent and may be the same or different, each independently represent a hydrogen atom, a linear or branched alkyl group having 1 to 50 carbon atoms, or a phenyl group, each independently represent a silicone chain represented by the general formula (6), ... 2 R ′ is a group having a polyglycerin group structure represented by general formula (4)-1 or general formula (4-2), 3 ' are each independent and may be the same or different; 1 ' group or the R 2 ' group, R 4 ' are each independent and may be the same or different; 1 ' group, the R 2 R is a ' group or an oxygen atom. 4 If ' is an oxygen atom, then two R 4 The a' groups may be bonded to form a single ether group to form a ring together with the silicon atom. a' may be the same or different and is 0 to 100, b' is 0 to 100, and a'+b' is 0 to 200. However, when b' is 0, R 3 At least one of the R 2 ' group. R 5 ' is an alkylene group having 2 to 10 carbon atoms or an aralkylene group having 7 to 10 carbon atoms; R 6 ', R 7 ' is an alkylene group having 2 to 6 carbon atoms, and R 7 ' may be an ether group, c' is 0 to 20, and d' is 1 to 20.)
[0030] A bioelectrode composition containing a silicone compound having such a polyglycerin structure can exhibit better moisturizing properties, and as a result, can form a biocontact layer that can exhibit better sensitivity to ions released from the skin.
[0031] The bioelectrode composition of the present invention may further contain a resin component (D) which is at least one selected from silicone-based resins, acrylic-based resins, and urethane-based resins.
[0032] The resin component (D) to be contained in the bioelectrode composition can be selected according to the properties to be imparted to the biocontact layer.
[0033] The resin component (D) is R x SiO (4-x) / 2 The silicone resin may contain any one of a silicone resin having a unit (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5) and a SiO2 unit, a diorganosiloxane having an alkenyl group, and an organohydrogenpolysiloxane having a SiH group.
[0034] Such a resin component (D) is compatible with the polymer compound (A) and can prevent the elution of salts, and can also impart higher adhesion to the bioelectrode composition.
[0035] The bioelectrode composition of the present invention may further contain an organic solvent (E).
[0036] The bioelectrode composition containing the organic solvent (E) can exhibit high coatability.
[0037] The bioelectrode composition of the present invention may further contain, as component (F), carbon powder, silver powder, silicon powder, and / or lithium titanate powder.
[0038] The carbon powder and the silver powder act as a conductivity enhancer and can impart better conductivity to the biocontact layer formed from the bioelectrode composition, while the silicon powder and the lithium titanate powder can further increase the ion reception sensitivity of the biocontact layer formed from the bioelectrode composition.
[0039] The carbon powder is preferably either or both of carbon black and carbon nanotubes.
[0040] By including such carbon powder, higher electrical conductivity can be provided.
[0041] The present invention also provides a conductive substrate, A living body contact layer formed on the conductive substrate; A bioelectrode having The present invention provides a bioelectrode in which the biocontact layer comprises a cured product of the bioelectrode composition of the present invention.
[0042] The bioelectrode of the present invention has a biocontact layer containing the cured product of the above-mentioned bioelectrode composition, and therefore has excellent electrical conductivity and biocompatibility, is lightweight, and can be manufactured at low cost. It is possible to prevent a significant decrease in electrical conductivity whether it is wet or dry, is transparent and has excellent design properties, does not leave any residue on the skin, and can be attached to the skin to quickly collect signals.
[0043] The conductive substrate may contain at least one selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, and carbon.
[0044] In this manner, various conductive substrates can be used in the bioelectrode of the present invention.
[0045] It is also preferable that the living body contact layer has been subjected to a humidification treatment.
[0046] A bioelectrode including such a biocontact layer can collect signals more quickly when attached to the skin.
[0047] The present invention also provides a method for producing a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, comprising the steps of: The bioelectrode composition of the present invention is applied onto a conductive substrate and cured to form a biocontact layer. The present invention provides a method for producing a bioelectrode, comprising the steps of:
[0048] According to this manufacturing method, it is possible to easily manufacture, at low cost, a bioelectrode that is highly conductive and biocompatible, lightweight, does not experience a significant decrease in conductivity whether it is wet or dry, is transparent and has excellent design properties, and can be attached to the skin to quickly collect signals.
[0049] The conductive substrate may contain at least one material selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, and carbon.
[0050] In this manner, in the method for producing a bioelectrode of the present invention, various conductive substrates can be used.
[0051] In this case, after the formation of the living body contact layer, it is preferred to immerse the living body contact layer in water or to subject the living body contact layer to a humidifying treatment.
[0052] This makes it possible to more effectively utilize the moisturizing effect of the living body contact layer. Effect of the Invention
[0053] As described above, the bioelectrode composition of the present invention has excellent electrical conductivity and biocompatibility, is lightweight, and can be manufactured at low cost. It can prevent a significant decrease in electrical conductivity whether it is wet or dry. It is transparent and has excellent design properties, can be attached to the skin to quickly collect signals, and can form a biocontact layer for a bioelectrode that does not leave any residue on the skin. [Brief description of the drawings]
[0054] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a bioelectrode of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of the bioelectrode of the present invention attached to a living body. [Diagram 3] FIG. 2 is a schematic diagram of a bioelectrode produced in an example of the present invention after printing. [Figure 4] FIG. 2 is a schematic diagram showing one of the bioelectrodes produced in the examples of the present invention cut out and with an adhesive layer attached. [Diagram 5] FIG. 2 is a diagram showing the locations where electrodes and a ground are attached to the human body when measuring a biosignal in an embodiment of the present invention. [Figure 6] 1 is an electrocardiogram waveform obtained using a bioelectrode according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0055] As described above, there has been a need to develop a bioelectrode composition that can be attached to the skin to quickly collect signals and form a biocontact layer for a bioelectrode that does not leave any residue on the skin, a bioelectrode in which a biocontact layer is formed from the bioelectrode composition, and a method for manufacturing the same.
[0056] Sodium, potassium, and calcium ions are released from the skin surface in tandem with the heartbeat. Bioelectrodes need to convert the increase or decrease in the number of ions released from the skin into an electrical signal. To do this, materials with excellent ionic conductivity are required to transmit the increase or decrease in ions.
[0057] When the acidity of the acid that forms the neutralized salt is high, the ions are strongly polarized, improving the ionic conductivity. This is why lithium salts of bis(trifluoromethanesulfonyl)imide acid and tris(trifluoromethanesulfonyl)methide acid exhibit high ionic conductivity as electrolytes in lithium-ion batteries. On the other hand, the higher the acid strength of the acid before it becomes a neutralized salt, the stronger the bioirritation of the salt. In other words, there is a trade-off between ionic conductivity and bioirritation. However, salts to be applied to bioelectrodes must have both high ionic conductivity and low bioirritation.
[0058] The larger the molecular weight of an ionic compound, the less permeable it is to the skin, and the less irritating it is to the skin. For this reason, a high molecular weight polymer type ionic compound is preferable. Therefore, the present inventors have synthesized a polymer obtained by polymerizing an ionic compound having a polymerizable double bond, i.e., a polymer compound (A), and found that by adding this, it is possible to construct a bioelectrode that is sensitive to the increase and decrease in the number of ions released from the skin.
[0059] The aforementioned Patent Documents 7, 8, and 9 show copolymers of strongly acidic ionic repeating units, repeating units having silicone chains, and hydrophilic repeating units such as polyether. The ionic repeating units and hydrophilic repeating units are necessary units to express and enhance ionic conductivity by their combination. However, if this is the only solution, the hydrophilicity may be too high and when the bioelectrode membrane comes into contact with water or sweat, the ionic polymer may dissolve in water and biosignals may not be obtained. For this reason, it is necessary to make the ionic polymer water-insoluble, and for this reason, a repeating unit having a silicone chain is copolymerized.
[0060] By adding an ionic polymer having an ionic repeating unit, a hydrophilic repeating unit, and a repeating unit having hydrophobic silicone to a silicone adhesive, ionic conductivity is exhibited, and a biosignal can be obtained. The mechanism by which ionic conductivity occurs in silicone adhesive, which is originally an insulator, is thought to be the microphase separation structure of the ionic polymer. Nafion, which has excellent ionic conductivity, is said to exhibit high ionic conductivity due to microphase separation between the hydrophilic sulfonic acid portion and the hydrophobic fluoropolymer portion.
[0061] If more significant microphase separation can be formed in ionic polymers for bioelectrodes, it is believed that it will be possible to form dry electrodes that have higher ionic conductivity and can obtain more sensitive biosignals.
[0062] The inventors have also found that the effect of preventing an ionic polymer having an ionic repeating unit, a hydrophilic repeating unit, and a repeating unit having hydrophobic silicone from dissolving in water can be improved by adding one or more types of filler particles selected from silica particles, alumina particles, titania particles, and zirconia particles. When the bioelectrode compositions of Patent Documents 7, 8, and 9 described above are immersed in water, there is a risk that the ionic polymer will dissolve in water. However, by adding silica particles, the interaction between silicon atoms is further strengthened, and a bioelectrode composition in which the components do not dissolve even in water can be obtained.
[0063] Here, in order to further improve the ionic conductivity, it is effective to add a hygroscopic material. The above-mentioned Patent Documents 7, 8, and 9 show the addition of a polyether silicone compound. Further, as a hygroscopic material, a silicone compound having polyglycerin can be mentioned. Polyglycerin, which has not only a polyether group but also a hydroxyl group, has high hygroscopicity, and high ionic conductivity can be obtained by combining a compound in which this is bonded to a silicone chain with an ionic polymer. When polyglycerin silicone is added, the ionic conductivity is improved, but due to a decrease in crosslink density, residues may be generated on the skin after the bioelectrode membrane is peeled off from the skin. In this case, the strength of the bioelectrode membrane is improved by adding silica particles, and the generation of residues after peeling can be suppressed.
[0064] In other words, the bioelectrode composition of the present invention has excellent electrical conductivity and biocompatibility, is lightweight, can be manufactured at low cost, can prevent a significant decrease in electrical conductivity whether it is wet or dry, can be attached to the skin to quickly collect signals, does not leave any residue on the skin, and can form a biocontact layer for a bioelectrode that is transparent and has excellent design properties.
[0065] That is, the present invention relates to a polymer compound (A) containing a repeating unit a having a structure selected from the group consisting of an ammonium salt, a sodium salt, a potassium salt, and a silver salt of any one of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide; one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles; The bioelectrode composition is characterized by containing each of the following:
[0066] The present invention will be described in detail below, but the present invention is not limited thereto.
[0067] <Bioelectrode composition> The bioelectrode composition of the present invention contains a polymer compound (polymer) (A) having an ionic repeating unit and one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles.
[0068] For example, the bioelectrode composition of the present invention may further contain a compound having a polyglycerin structure (C), a resin component (D), a metal powder, a carbon powder, a silicon powder, a lithium titanate powder, a tackifier, a crosslinking agent, a crosslinking catalyst, an ionic additive and / or an organic solvent (E). Each component will be described in more detail below.
[0069] [High molecular compound (A)] The polymer compound (A) incorporated in the bioelectrode composition of the present invention can be called, for example, an ionic material (conductive material). Specifically, the polymer compound (A) is a polymer containing a repeating unit a having a structure selected from the ammonium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide. Therefore, the polymer compound (A) can also be called a salt.
[0070] The polymer compound (A) contained in the bioelectrode composition of the present invention can conduct electricity by ionic conduction. That is, the bioelectrode composition of the present invention can exhibit high ionic conductivity, and therefore can exhibit excellent electrical conductivity.
[0071] In addition, the polymer compound (A) contained in the bioelectrode composition of the present invention can exhibit a sufficiently low acidity to achieve low bioirritation.
[0072] The repeating unit a preferably has a structure represented by any one of the following general formulas (1)-1 to (1)-4. [ka] (In the general formula (1)-1, Rf1 and Rf2 are a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group. When Rf1 and Rf2 are oxygen atoms, Rf1 and Rf2 are one oxygen atom bonding to one carbon atom to form a carbonyl group, Rf3 and Rf4 are a hydrogen atom, a fluorine atom, or a trifluoromethyl group, and at least one of Rf1 to Rf4 is a fluorine atom or a trifluoromethyl group. In the general formulas (1)-2, (1)-3, and (1)-4, Rf5, Rf6, and Rf7 are each a fluorine atom, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom. In the general formulas (1)-1 to (1)-4, M + is an ion selected from an ammonium ion, a sodium ion, a potassium ion, and a silver ion. In the general formula (1)-2, m is an integer of 1 to 4.
[0073] When the repeating unit a has such a structure, it is possible to obtain a bioelectrode composition capable of forming a biocontact layer for a bioelectrode having superior electrical conductivity and biocompatibility.
[0074] It is more preferable that the repeating unit a has at least one type selected from the repeating units a1 to a7 represented by the following general formula (2). [ka] (In general formula (2), R 1 , R 3 , R 5 , R 8 , R 10 , R 11 , and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 , and R 14R are each independently a single bond or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms. The hydrocarbon group may have an ester group, an ether group, or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 In the formula, one or two of the hydrogen atoms may be substituted with a fluorine atom. Each of X1, X2, X3, X4, X6, and X7 is independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, and X5 is a single bond, an ether group, or an ester group. Y is an oxygen atom or -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 may form a ring together with Rf1' and Rf5' are a fluorine atom, a trifluoromethyl group, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6, and a7 are each 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0≦a7≦1.0, <a1+a2+a3+a4+a5+a6+a7≦1.0である。M + is an ion selected from ammonium ion, sodium ion, potassium ion, and silver ion.
[0075] If the repeating unit a has such a structure, it is possible to obtain a bioelectrode composition capable of forming a biocontact layer for a bioelectrode having even better electrical conductivity and biocompatibility.
[0076] In addition, a1, a2, a3, a4, a5, a6, and a7 are symbols for identifying each repeating unit and correspond to the proportion of each repeating unit in the polymer compound (A). That is, in the above general formula (2), the repeating units a1, a2, a3, a4, and a5 are shown in order from left to right in the upper row, and the repeating units a6 and a7 are shown in order from left to right in the lower row.
[0077] Among the repeating units a1 to a7 represented by the above general formula (2), specific examples of the fluorosulfonate monomer for obtaining the repeating units a1 to a5 are shown below.
[0078] [ka]
[0079] [ka]
[0080] [ka]
[0081] [ka]
[0082] [ka]
[0083] [ka]
[0084] [ka]
[0085] [ka]
[0086] [ka]
[0087]
change
[0088]
change
[0089]
change
[0090]
change
[0091]
change
[0092]
change
[0093]
change
[0094]
change
[0095]
change
[0096]
change
[0097]
change
[0098] [ka]
[0099] Specific examples of the sulfonimide salt monomer for obtaining the repeating unit a6 of the above general formula include those shown below.
[0100] [ka]
[0101] [ka]
[0102] [ka]
[0103] [ka]
[0104] [ka]
[0105] Specific examples of N-carbonylsulfonamide salt monomers for obtaining the repeating unit a7 of the above general formula are shown below. [ka]
[0106] [ka] (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R11 , and R 13 As mentioned above.)
[0107] Furthermore, the polymer compound (A) (component (A)) contains, as an ammonium ion constituting an ammonium salt, particularly M in the repeating unit a (repeating units a1 to a7). + It is preferable that the ammonium ion (ammonium cation) is contained in the following general formula (3). [ka] (In general formula (3), R 101d , R 101e , R 101f and R 101g R is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 14 carbon atoms, a linear, branched, or cyclic alkenyl group or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more groups selected from an ether group, a carbonyl group, an ester group, a hydroxy group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d and R 101e , or R 101d , R 101e and R 101f may form a ring together with the nitrogen atom to which they are attached, and when they form a ring, R 101d and R 101e , or R 101d , R 101e and R 101f is an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having the nitrogen atom in the general formula (3) in the ring.
[0108] Specific examples of the ammonium ion represented by the above general formula (3) include the following.
[0109] [ka]
[0110]
change
[0111]
change
[0112]
change
[0113]
change
[0114]
change
[0115]
change
[0116]
change
[0117]
change
[0118]
change
[0119]
change
[0120]
change
[0121] [ka]
[0122] [ka]
[0123] [ka]
[0124] [ka]
[0125] As the ammonium ion represented by the above general formula (3), a tertiary or quaternary ammonium ion is particularly preferred.
[0126] (Repeating unit b) In addition to the repeating units a1 to a7, the polymer compound (A) (component (A)) of the bioelectrode composition of the present invention can also be copolymerized with a repeating unit b having a glyme chain in order to improve electrical conductivity. Specific examples of monomers for obtaining the repeating unit b having a glyme chain are shown below. Copolymerization of a repeating unit having a glyme chain can promote the movement of ions released from the skin in the biocontact layer (dry electrode film), thereby increasing the sensitivity of the bioelectrode (dry electrode).
[0127] [ka]
[0128] [ka]
[0129] [ka]
[0130] [ka] In the above formula, R is a hydrogen atom or a methyl group.
[0131] (Repeating unit c) In addition to the repeating units a1 to a7 and any repeating unit b, the polymer compound (A) (component (A)) of the bioelectrode composition of the present invention can also be copolymerized with a hydrophilic repeating unit c having a hydrophilic group such as a hydroxyl group, a carboxyl group, an ammonium salt, a betaine, an amide group, a pyrrolidone, a lactone ring, a lactam ring, a sultone ring, a sodium salt of sulfonic acid, and a potassium salt of sulfonic acid in order to improve electrical conductivity. Specific examples of monomers for obtaining the hydrophilic repeating unit c are shown below. By copolymerizing repeating units containing these hydrophilic groups, it is possible to increase sensitivity to ions released from the skin and increase the sensitivity of the bioelectrode (dry electrode).
[0132] [ka]
[0133] [ka]
[0134] [ka] In the above formula, R is a hydrogen atom or a methyl group.
[0135] (Repeating unit d) The polymer compound (A) in the bioelectrode composition of the present invention can have a repeating unit d that imparts adhesiveness. Specific examples of monomers from which the repeating unit d can be obtained include the following.
[0136] [ka]
[0137] [ka]
[0138] [ka]
[0139] [ka]
[0140] [ka]
[0141] (Repeating unit e) Furthermore, a crosslinkable repeating unit e can also be copolymerized. Examples of the crosslinkable repeating unit e include a repeating unit having an oxirane ring or an oxetane ring.
[0142] Specific examples of monomers for obtaining the repeating unit e having an oxirane ring or oxetane ring include those shown below. [ka]
[0143] [ka] Here, R is a methyl group or a hydrogen atom.
[0144] (Repeating unit f) The polymer compound (A) (component (A)) of the bioelectrode composition of the present invention can have a silicon-containing repeating unit f in addition to the repeating units a1 to a7 and any repeating unit selected from b to e. Specifically, the following can be exemplified.
[0145] [ka] n is an integer from 0 to 100.
[0146] [ka]
[0147] (Repeating unit g) The polymer compound (A) (component (A)) of the bioelectrode composition of the present invention can have a fluorine-containing repeating unit g in addition to the above repeating units a1 to a7 and any repeating unit selected from b to f.
[0148] Specific examples of monomers from which the fluorine-containing repeating unit g can be obtained include the following.
[0149] [ka]
[0150] [ka]
[0151] [ka]
[0152] [ka]
[0153] [ka]
[0154] [ka]
[0155] [ka]
[0156] Here, R is a hydrogen atom or a methyl group.
[0157] One method for synthesizing the polymer compound (A) that is the component (A) can be a method in which desired monomers among those that give the repeating units a1 to a7, b, c, d, e, f, and g are polymerized by heating in an organic solvent with the addition of a radical polymerization initiator to obtain a polymer compound copolymer.
[0158] Examples of the organic solvent used during polymerization include toluene, benzene, tetrahydrofuran, diethyl ether, dioxane, etc. Examples of the polymerization initiator include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile), dimethyl 2,2-azobis(2-methylpropionate), benzoyl peroxide, lauroyl peroxide, etc. The heating temperature is preferably 50 to 80°C, and the reaction time is preferably 2 to 100 hours, more preferably 5 to 20 hours.
[0159] Here, the ratios of the repeating units a1 to a7, b, c, d, e, f, and g in the polymer compound (A) (polymer (A)) are such that 0 ≤ a1 ≤ 1.0, 0 ≤ a2 ≤ 1.0, 0 ≤ a3 ≤ 1.0, 0 ≤ a4 ≤ 1.0, 0 ≤ a5 ≤ 1.0, 0 ≤ a6 ≤ 1.0, 0 ≤ a7 ≤ 1.0, 0 < a1 + a2 + a3 + a4 + a5 + a6 + a7 ≤ 1.0, 0 ≤ b < 1.0, 0 ≤ c < 1.0, 0 ≤ d < 1.0, 0 ≤ e < 0.9, 0 ≤ f < 0.9, 0 ≤ g < 0.9, preferably 0 ≤ a1 ≤ 0.9, 0 ≤ a2 ≤ 0.9, 0 ≤ a3 ≤ 0.9, 0 ≤ a4 ≤ 0.9, 0 ≤ a5 ≤ 0.9, 0 ≤ a6 ≤ 0.9, 0 ≤ a7 ≤ 0.9, 0.01 ≤ a1 + a2 + a3 + a4 + a5 + a6 + a7 ≤ 0.9, 0.03 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.8, 0 ≤ d ≤ 0.8, 0 ≤ e < 0.8, 0 ≤ f < 0.8, 0 ≤ g < 0.8, more preferably 0 ≤ a1 ≤ 0.8, 0 ≤ a2 ≤ 0.8, 0 ≤ a3 ≤ 0.8, 0 ≤ a4 ≤ 0.8, 0 ≤ a5 ≤ 0.8, 0 ≤ a6 ≤ 0.8, 0 ≤ a7 ≤ 0.8, 0.02 ≤ a1 + a2 + a3 + a4 + a5 + a6 + a7 ≤ 0.8, 0.05 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.7, 0 ≤ d ≤ 0.5, 0 ≤ e < 0.3, 0 ≤ f < 0.7, 0 ≤ g < 0.7.
[0160] Note that, for example, a1 + a2 + a3 + a4 + a5 + a6 + a7 + b + c + d + e + f + g = 1 means that in the polymer compound (A) containing the repeating units a1, a2, a3, a4, a5, a6, a7, b, c, d, e, f, and g, the total amount of the repeating units a1, a2, a3, a4, a5, a6, a7, b, c, d, e, f, and g is 100 mol% with respect to the total amount of all repeating units. And a1 + a2 + a3 + a4 + a5 + a6 + a7 + b + c + d + e + f + g < 1 means that the total amount of the repeating units a1, a2, a3, a4, a5, a6, a7, b, c, d, e, f, and g is less than 100 mol% with respect to the total amount of all repeating units, that is, it indicates that the polymer compound (A) has other repeating units in addition to the repeating units a1, a2, a3, a4, a5, a6, a7, b, c, d, e, f, and g.
[0161] The molecular weight of the polymer compound (A) ((A) component) is preferably 500 or more as weight average molecular weight, more preferably 1,000 or more and 1,000,000 or less, and even more preferably 2,000 or more and 500,000 or less. In addition, if the amount of ionic monomer (residual monomer) that is not incorporated into the (A) component after polymerization is small, there is no risk of this monomer penetrating into the skin and causing allergies in a biocompatibility test, so it is preferable to reduce the amount of the residual monomer. The amount of the residual monomer is preferably 10 parts by mass or less per 100 parts by mass of the total (A) component. In addition, as the (A) component, one type of polymer compound may be used alone, or a mixture of two or more types of polymer compounds with different molecular weights, dispersities, or polymerizable monomers may be used. The weight average molecular weight of the polymer compound (A) can be confirmed by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.
[0162] [Filler particles (B)] The bioelectrode composition of the present invention is characterized by containing one or more kinds of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles. The filler particles (B) can increase the sensitivity of ion reception. The amount of the filler particles (B) is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin including the polymer compound (A) and the resin component (D) described below. The filler particles (B) may be used alone or in combination of two or more kinds.
[0163] In the bioelectrode composition of the present invention, one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles increase the sensitivity of ion reception of the biocontact layer formed from the bioelectrode composition, so that biosignals can be obtained quickly even without conductive particles.
[0164] In addition, one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles contained in the bioelectrode composition of the present invention can interact with the water-soluble silicone-containing composition contained in the bioelectrode composition and prevent it from dissolving in water.
[0165] In addition, the one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles contained in the bioelectrode composition of the present invention can adjust the viscosity during printing and also make the appearance after printing transparent, thereby improving the design.
[0166] Furthermore, among the silica particles, alumina particles, titania particles, and zirconia particles contained in the bioelectrode composition of the present invention, the use of silica particles is particularly preferred. The silica particles have a particularly strong interaction with the silicone-containing compound contained in the bioelectrode composition of the present invention, and can improve the effect of preventing the combined component of the polymer compound (A) and the compound (C) having a polyglycerin structure described below from dissolving into water from the bioelectrode composition.
[0167] Silica particles, alumina particles, titania particles, and zirconia particles may be used in an untreated state, or may be surface-treated with an organic compound as necessary.For example, the surface may be treated with a hydrophilic group such as alcohol or carboxylic acid, a silane having a hydrophilic group such as a hydroxyl group, a carboxyl group, an amino group, or a thiol group, or a hydrophobic group such as polydimethylsiloxane, a silane having an alkyl group, or hexamethyldisilazane.In addition, among silica particles, alumina particles, titania particles, and zirconia particles, the use of silica particles is particularly preferred in terms of biocompatibility and affinity with the bioelectrode composition.
[0168] The average diameter of the silica particles, alumina particles, titania particles, and zirconia particles is preferably 0.001 μm to 20 μm. When the bioelectrode composition of the present invention is to be transparent, the particle diameter is preferably 0.001 μm to 2 μm, more preferably 0.001 μm to 0.1 μm, and particularly preferably 0.001 μm to 0.01 μm.
[0169] In the present invention, the particle size can be determined by a laser diffraction method.
[0170] The shape of the silica particles, alumina particles, titania particles and zirconia particles is selected from spherical, hollow, porous, rod-like, plate-like, fibrous, and amorphous powders, and is preferably spherical.
[0171] If the composition contains such silica particles, alumina particles, titania particles, or zirconia particles, the affinity with silicone can suppress the elution of the water-soluble polymeric compound (A) having the repeating unit a, and the composition can be used to form a transparent, design-friendly biocontact layer for a bioelectrode that does not leave any residue on the skin and that can increase the ion reception sensitivity of the biocontact layer formed from the bioelectrode composition.
[0172] The silica used may be wet or dry fumed silica, fused silica, etc. For example, hydrophobic surface-treated silica such as Aerosil 200 (average particle size: 12 nm), Aerosil 300 (average particle size: 7 nm), Aerosil RX200, Aerosil RX300, and Aerosil RY300 manufactured by Nippon Aerosil Co., Ltd., and Leosil HM-30S manufactured by Tokuyama, fumed silica manufactured by Aldrich, and Admafine manufactured by Admatechs Co., Ltd. may be used.
[0173] [Compounds (C) having a polyglycerol structure] The bioelectrode composition of the present invention may further contain a compound (C) having a polyglycerin structure (component (C)) in addition to the polymer compound (A) and the filler particles (B). The amount of component (C) is preferably 0.01 to 100 parts by mass, more preferably 0.5 to 60 parts by mass, per 100 parts by mass of component (A). The component (C) may be used alone or in combination of two or more kinds. The compound (C) having a polyglycerin structure is preferably a silicone compound having a polyglycerin structure.
[0174] The silicone compound having a polyglycerin structure is preferably represented by either of the following general formulas (4) and (5). [ka] (In the formula, R 1 are each independent and may be the same or different, each independently represent a hydrogen atom, a linear or branched alkyl group having 1 to 50 carbon atoms, or a phenyl group, each independently represent a silicone chain represented by the general formula (6), ... silicone chain represented by the general formula (6), each independently represent a silicone chain represented by the general formula (6), 2 R ′ is a group having a polyglycerin group structure represented by general formula (4)-1 or general formula (4-2), 3 ' are each independent and may be the same or different; 1 ' group or the R 2 ' group, R 4 ' are each independent and may be the same or different; 1 ' group, the R 2 R is a ' group or an oxygen atom. 4 If ' is an oxygen atom, then two R 4 The a' groups may be bonded to form a single ether group to form a ring together with the silicon atom. a' may be the same or different and is 0 to 100, b' is 0 to 100, and a'+b' is 0 to 200. However, when b' is 0, R 3 At least one of the R 2 ' group. R 5 ' is an alkylene group having 2 to 10 carbon atoms or an aralkylene group having 7 to 10 carbon atoms; R 6 ', R 7 ' is an alkylene group having 2 to 6 carbon atoms, and R 7 ' may be an ether group, c' is 0 to 20, and d' is 1 to 20.)
[0175] Examples of such silicone compounds having a polyglycerin structure include the following.
[0176] [ka]
[0177] [ka]
[0178] [ka]
[0179] [ka]
[0180] [ka]
[0181] [ka]
[0182] [ka]
[0183] [ka]
[0184] [ka]
[0185] [ka] (wherein a', b', c' and d' are as defined above).
[0186] If the silicone compound having such a polyglycerin structure is included, it can exhibit better moisture retention, and as a result, it is possible to obtain a bioelectrode composition capable of forming a biocontact layer that exhibits better sensitivity to ions released from the skin. When the polymer compound (A) or the filler particles (B) have moisture retention, the silicone compound having a polyglycerin structure is not necessarily required.
[0187] [Resin component (D)] The bioelectrode composition of the present invention may further contain a resin component (D) in addition to the polymer compound (A) and the filler particles (B). For example, the bioelectrode composition of the present invention may further contain a resin component (D) which is one or more selected from a silicone resin, an acrylic resin, and a urethane resin. By including one or more resins selected from a silicone resin, an acrylic resin, and a urethane resin, a bioelectrode including a biocontact layer having excellent elasticity can be provided. Here, it is preferable to use a silicone resin different from a silicone compound having a polyglycerin structure.
[0188] The resin component (D) that can be blended in the bioelectrode composition of the present invention can be, for example, a component that is compatible with the above-mentioned polymer compound (A) (ionic material (salt)) to prevent the elution of salt and to exhibit adhesiveness. When the bioelectrode composition contains metal powder, carbon powder, silicon powder, lithium titanate powder, etc., as described below, the resin component (D) can hold these powders. When the polymer compound (A) has adhesiveness, the resin component (D) is not necessarily required. Note that the resin component (D) may be any resin other than the above-mentioned component (A), and is preferably either a thermosetting resin or a photocurable resin, or both of these, and is particularly preferably one or more selected from silicone-based resins, acrylic resins, and urethane-based resins other than silicone compounds having a polyglycerin structure.
[0189] Examples of adhesive silicone-based resins include those that are cured by addition reaction or radical crosslinking reaction. Examples of the addition reaction cured type include diorganosiloxane having an alkenyl group, RSiO, as described in JP 2015-193803 A. 0.5 and SiO2 units, organohydrogenpolysiloxane having a plurality of SiH groups, platinum catalyst, addition reaction inhibitor, and organic solvent. In addition, as the radical crosslinking reaction curing type, for example, diorganopolysiloxane which may or may not have alkenyl groups, R3SiO 0.5 and those containing an MQ resin having SiO2 units, an organic peroxide, and an organic solvent, where R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.
[0190] It is also possible to use a polysiloxane-resin integrated compound formed by condensing polysiloxane with silanols at the polymer end or side chain with MQ resin. MQ resin contains a lot of silanols, so adding this improves adhesive strength, but since it is not crosslinkable, it is not molecularly bonded to the polysiloxane. By integrating polysiloxane and resin as described above, adhesive strength can be increased.
[0191] In addition, modified siloxanes having a group selected from amino groups, oxirane groups, oxetane groups, polyether groups, hydroxy groups, carboxyl groups, mercapto groups, methacryl groups, acrylic groups, phenol groups, silanol groups, carboxylic anhydride groups, aryl groups, aralkyl groups, amide groups, ester groups, and lactone rings can be added to silicone resins. By adding modified siloxanes, the dispersibility of component (A) in the silicone resin is improved. The modified siloxanes may be modified at one end, both ends, or the side chains of the siloxane.
[0192] The adhesive acrylic resin may be, for example, one having a hydrophilic (meth)acrylic acid ester or a long-chain hydrophobic (meth)acrylic acid ester as a repeating unit, as described in JP 2016-011338 A. In some cases, a (meth)acrylic acid ester having a functional group or a (meth)acrylic acid ester having a siloxane bond may be copolymerized.
[0193] As the adhesive urethane-based resin, for example, one having a urethane bond and a polyether or polyester bond, a polycarbonate bond, or a siloxane bond, as described in JP 2016-065238 A, can be used.
[0194] In addition, in order to prevent the decrease in conductivity due to the elution of the (A) component from the biocontact layer, in the bioelectrode composition of the present invention, it is preferable that the resin component (D) has high compatibility with the above-mentioned (A) component. In addition, in order to prevent the peeling of the biocontact layer from the conductive substrate, it is preferable that the resin component (D) has high adhesion to the conductive substrate in the bioelectrode composition of the present invention. In order to make the resin of the (D) component highly compatible with the conductive substrate and salt, it is effective to use a resin with high polarity. Examples of such resins include resins having one or more selected from ether bonds, ester bonds, amide bonds, imide bonds, urethane bonds, thiourethane bonds, and thiol groups, or polyacrylic resins, polyamide resins, polyimide resins, polyurethane resins, and polythiourethane resins. On the other hand, since the biocontact layer contacts the living body, it is easily affected by sweat from the living body. Therefore, in the bioelectrode composition of the present invention, it is preferable that the resin component (D) has high water repellency and is not easily hydrolyzed. In order to make the resin of the (D) component highly water repellent and not easily hydrolyzed, it is effective to use a resin containing silicon.
[0195] Silicon-atom-containing polyacrylic resins include polymers having silicone in the main chain and polymers having silicon atoms in the side chain, and both can be used suitably. As the polymer having silicone in the main chain, siloxane or silsesquioxane having a (meth)acrylpropyl group can be used. In this case, the (meth)acryl portion can be polymerized and cured by adding a photoradical generator.
[0196] Suitable examples of polyamide resins containing silicon atoms include polyamide silicone resins described in JP 2011-079946 A and U.S. Patent No. 5,981,680 A. Such polyamide silicone resins can be synthesized by combining, for example, a silicone having amino groups at both ends or a non-silicone compound having amino groups at both ends with a non-silicone having carboxyl groups at both ends or a silicone having carboxyl groups at both ends.
[0197] Alternatively, polyamic acid obtained by reacting a carboxylic anhydride with an amine before cyclization may be used. An epoxy or oxetane crosslinking agent may be used to crosslink the carboxyl groups of the polyamic acid, or the carboxyl groups may be esterified with hydroxyethyl (meth)acrylate to perform photoradical crosslinking of the (meth)acrylate portion.
[0198] As the polyimide resin containing silicon atoms, for example, the polyimide silicone resin described in JP-A-2002-332305 can be suitably used. Polyimide resins have a very high viscosity, but the viscosity can be reduced by blending a (meth)acrylic monomer as a solvent and a crosslinking agent.
[0199] Examples of polyurethane resins containing silicon atoms include polyurethane silicone resins. In such polyurethane silicone resins, crosslinking by urethane bonds can be performed by blending and heating a compound having isocyanate groups at both ends and a compound having hydroxyl groups at the ends. In this case, it is necessary to contain silicon atoms (siloxane bonds) in either or both of the compound having isocyanate groups at both ends and the compound having hydroxyl groups at the ends. Alternatively, as described in JP 2005-320418 A, a urethane (meth)acrylate monomer can be blended with polysiloxane to cause photocrosslinking. In addition, a polymer having both siloxane bonds and urethane bonds and (meth)acrylate groups at the ends can also be photocrosslinked. In particular, the silicone chain is attached to the side chain described in JP 2018-123304 A and JP 2019-70109 A, and the polyurethane of the main chain has high strength and high elasticity properties, which is preferable.
[0200] The polythiourethane resin containing silicon atoms can be obtained by reacting a compound having a thiol group with a compound having an isocyanate group, and any one of them may contain a silicon atom. In addition, if the compound has a (meth)acrylate group at the end, it can be photocured.
[0201] In the silicone resin, the above-mentioned diorganosiloxane having an alkenyl group, RSiO 0.5 In addition to the MQ resin having SiO2 units and the organohydrogenpolysiloxane having multiple SiH groups, the compatibility with the above-mentioned salts can be improved by adding a modified siloxane having a group selected from amino groups, oxirane groups, oxetane groups, polyether groups, hydroxyl groups, carboxyl groups, mercapto groups, methacryl groups, acrylic groups, phenol groups, silanol groups, carboxylic anhydride groups, aryl groups, aralkyl groups, amide groups, ester groups, and lactone rings.
[0202] In the bioelectrode composition of the present invention, the blending amount of the resin component (D) is preferably 0 to 2,000 parts by mass, more preferably 10 to 1,000 parts by mass, per 100 parts by mass of the polymer compound (A) which is an ionic polymer. The resin component (D) may be used alone or in combination of two or more kinds.
[0203] As described later, the biocontact layer of the bioelectrode of the present invention is a cured product of the bioelectrode composition of the present invention. By curing the bioelectrode composition, the adhesion of the biocontact layer to both the skin and the conductive substrate becomes good. The curing method is not particularly limited, and a general method can be used, for example, heat and / or light, or a crosslinking reaction using an acid or base catalyst. The crosslinking reaction can be carried out by appropriately selecting a method described in, for example, Crosslinking Reaction Handbook, Nakayama Hiroharu, Maruzen Publishing (2013), Chapter 2, p. 51 to p. 371.
[0204] Diorganosiloxanes having alkenyl groups and organohydrogenpolysiloxanes having multiple SiH groups can be crosslinked by an addition reaction in the presence of a platinum catalyst.
[0205] Examples of platinum catalysts include platinum catalysts such as chloroplatinic acid, alcohol solutions of chloroplatinic acid, reaction products of chloroplatinic acid and alcohol, reaction products of chloroplatinic acid and olefin compounds, reaction products of chloroplatinic acid and vinyl group-containing siloxane, platinum-olefin complexes, platinum-vinyl group-containing siloxane complexes, and platinum group metal catalysts such as rhodium complexes and ruthenium complexes. Furthermore, these catalysts may be used in the form of a solution or dispersion in an alcohol-based, hydrocarbon-based, or siloxane-based solvent.
[0206] The amount of the platinum catalyst added is preferably within a range of 5 to 2,000 ppm, particularly 10 to 500 ppm, per 100 parts by mass of the combined resin of the polymer compound (A) and the resin component (D).
[0207] When an addition-curing silicone resin is used, an addition reaction inhibitor may be added as a quencher to prevent the platinum catalyst from acting in the solution and in a low-temperature environment before heat curing after coating formation. Specific examples include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclohexanol, 3-methyl-3-trimethylsiloxy-1-butyne, 3-methyl-3-trimethylsiloxy-1-pentyne, 3,5-dimethyl-3-trimethylsiloxy-1-hexyne, 1-ethynyl-1-trimethylsiloxycyclohexane, bis(2,2-dimethyl-3-butynoxy)dimethylsilane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,1,3,3-tetramethyl-1,3-divinyldisiloxane.
[0208] The amount of the addition reaction inhibitor added is preferably within a range of 0 to 10 parts by mass, particularly 0.05 to 3 parts by mass, per 100 parts by mass of the combined resin of the polymer compound (A) and the resin component (D).
[0209] Methods for photocuring include using a resin having a (meth)acrylate end or an olefin end, adding a crosslinking agent whose end is a (meth)acrylate, olefin, or thiol group, and adding a photoradical generator that generates radicals when exposed to light, and using a resin or crosslinking agent having an oxirane group, oxetane group, or vinyl ether group, and adding a photoacid generator that generates acid when exposed to light.
[0210] Examples of photoradical generators include acetophenone, 4,4'-dimethoxybenzyl, benzyl, benzoin, benzophenone, 2-benzoylbenzoic acid, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzoin isobutyl ether, 4-benzoylbenzoic acid, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2-benzoylbenzoic acid methyl, 2-(1,3-benzodioxol-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-benzyl 2-(dimethylamino)-4'-morpholinobutyrophenone, 4,4'-dichlorobenzophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,4-diethylthioxanthen-9-one, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO), 1,4-dibenzoylbenzene, 2-ethylanthraquinone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylpropiophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-isonitrosopropiophenone, and 2-phenyl-2-(p-toluenesulfonyloxy)acetophenone.
[0211] It can also be cured by adding a thermally decomposable radical generator. Examples of thermally decomposable radical generators include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(methylpropionamidine) hydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]hydrochloride, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(cyclohexane-1-carbonitrile), 1[(1-cyano-1-methylethyl)azo]formamide, 2,2'-azobis[2-methyl- N-(2-hydroxyethyl)propionamide], 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), dimethyl-2,2'-azobis(isobutyrate), 4,4'-azobis(4-cyanopentanoic acid), dimethyl-2,2'-azobis(2-methylpropionate), benzoyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, di-tert-butyl peroxide, di-tert-amyl peroxide, di-n-butyl peroxide, and dicumyl peroxide.
[0212] Examples of the photoacid generator include sulfonium salts, iodonium salts, sulfonyldiazomethane, N-sulfonyloxyimide, and oxime-O-sulfonate type acid generators, etc. Specific examples of the photoacid generator include those described in paragraphs
[0122] to
[0142] of JP2008-111103A and JP2009-080474A.
[0213] The amount of the radical generator or photoacid generator added is preferably within a range of 0.1 to 50 parts by mass per 100 parts by mass of the combined resin of the polymer compound (A) and the resin component (D).
[0214] Among these, the resin of component (D) is R x SiO(4-x) / 2 Particularly preferred are those containing any of silicone resins having units (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5) and SiO2 units, diorganosiloxanes having alkenyl groups, and organohydrogenpolysiloxanes having SiH groups. Such resin component (D) is compatible with the polymer compound (A) and can prevent the elution of salt, and can impart higher adhesion to the bioelectrode composition.
[0215] [Organic solvent (E)] In addition, an organic solvent (E) can be added to the bioelectrode composition of the present invention. Specific examples of the organic solvent (E) include toluene, xylene, cumene, 1,2,3-trimethylbenzene, 1,2,4-trimethylbenzene, 1,3,5-trimethylbenzene, styrene, α-methylstyrene, butylbenzene, sec-butylbenzene, isobutylbenzene, cymene, diethylbenzene, 2-ethyl-p-xylene, 2-propyltoluene, 3-propyltoluene, 4-propyltoluene, 1,2,3,5-tetramethyltoluene, 1,2,4,5-tetramethyltoluene, ... Hydronaphthalene, 4-phenyl-1-butene, tert-amylbenzene, amylbenzene, 2-tert-butyltoluene, 3-tert-butyltoluene, 4-tert-butyltoluene, 5-isopropyl-m-xylene, 3-methylethylbenzene, tert-butyl-3-ethylbenzene, 4-tert-butyl-o-xylene, 5-tert-butyl-m-xylene, tert-butyl-p-xylene, 1,2-diisopropylbenzene, 1,3-diisopropylbenzene, 1,4- Aromatic hydrocarbon solvents such as diisopropylbenzene, dipropylbenzene, pentamethylbenzene, hexamethylbenzene, hexylbenzene, and 1,3,5-triethylbenzene, n-heptane, isoheptane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, 1,6-heptadiene, 5-methyl-1-hexyne, norbornane, norbornene, dicyclopentadiene, 1-methyl-1,4-cyclohexadiene, 1-heptyne, 2-heptyne, cycloheptane, cyclohexyne ... n-octane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, 3,4-dimethylhexane, 3,5-dimethylhexane, 3,6-dimethylhexane, 3,7-dimethylhexane, 3,8-dimethylhexane, 3,9-dimethylhexane, 4,10-dimethylhexane, 4,11-dimethylcyclohexane, 4,12-dimethylcyclohexane, 4,13-dimethylcyclohexane, 4,14-dimethylcyclohexane, 4,15-dimethylcyclohexane, 4,16-dimethylcyclohexane, 4,17-dimethylcyclohexane, 4,18-dimethylcyclohexane, 4,19-dimethylcyclohexane, 5,20-dimethylcyclohexane, 5,21-dimethylcyclohexane, 5,22-dimethylcyclohexane, 5,23-dimethylcyclohexane, 5,24-dimethylhexane, 5,25-dimethylcyclohexane, 5,26-dimethylcyclohexane, 5,27-dimethylcyclohexane, 5,28-dimethylcyclohexane, 5,29-dimethylcyclohexane, 5,30-dimethylcyclohexane, 5,31-dimethylcyclohexane, 5,32-dimethylcyclohexane, 5,33-dimethylcyclohexane, 5,34-dimethylcyclohexane, 5,35-dimethylcyclohexane, 5,36-dimethylcyclohexane, 5,37-dimethylcyclohexane, 5,38-dimethylcyclohexane, 5,39-dimethylcyclohexane, 5,40-dimethylcyclohexane, 5,41-dimethylcyclohexane, 5,42-dimethylcyclohexane, 5,43-dimethylcyclohexane, 5,44-dimethylcyclohexane, 5,45-dimethylcyclohexane, 5,46-dimethylcyclohexane, 5,47-dimethylcyclohexane, 5,48-dimethylcyclohexane, 5,49-dimethylcyclohexane, 5,48-dimethylcyclohexane, 5,49-dimethylcyclohexane4-Dimethylhexane, 3-ethyl-2-methylpentane, 3-ethyl-3-methylpentane, 2-methylheptane, 3-methylheptane, 4-methylheptane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane, cyclooctane, cyclooctene, 1,2-dimethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, ethylcyclohexane, vinylcyclohexane, isopropylcyclopentane, 2,2-dimethyl-3-hexene, 2,4-dimethyl-1-hexene, 2,5-dimethyl-1- Hexene, 2,5-dimethyl-2-hexene, 3,3-dimethyl-1-hexene, 3,4-dimethyl-1-hexene, 4,4-dimethyl-1-hexene, 2-ethyl-1-hexene, 2-methyl-1-heptene, 1-octene, 2-octene, 3-octene, 4-octene, 1,7-octadiene, 1-octyne, 2-octyne, 3-octyne, 4-octyne, n-nonane, 2,3-dimethylheptane, 2,4-dimethylheptane, 2,5-dimethylheptane, 3,3-dimethylheptane, 3,4-dimethylheptane, 3,5-dimethylheptane, 4-ethylhexene, ethylheptane, 2-methyloctane, 3-methyloctane, 4-methyloctane, 2,2,4,4-tetramethylpentane, 2,2,4-trimethylhexane, 2,2,5-trimethylhexane, 2,2-dimethyl-3-heptene, 2,3-dimethyl-3-heptene, 2,4-dimethyl-1-heptene, 2,6-dimethyl-1-heptene, 2,6-dimethyl-3-heptene, 3,5-dimethyl-3-heptene, 2,4,4-trimethyl-1-hexene, 3,5,5-trimethyl-1-hexene, 1-ethyl-2-methylcyclohexane, 1-ethyl-3 -Methylcyclohexane, 1-ethyl-4-methylcyclohexane, propylcyclohexane, isopropylcyclohexane, 1,1,3-trimethylcyclohexane, 1,1,4-trimethylcyclohexane, 1,2,3-trimethylcyclohexane, 1,2,4-trimethylcyclohexane, 1,3,5-trimethylcyclohexane, allylcyclohexane, hydrindane, 1,8-nonadiene, 1-nonyne, 2-nonyne, 3-nonyne, 4-nonyne, 1-nonene, 2-nonene, 3-nonene, 4-nonene, n-decane, 3,3-dimethyloctane, 3,5-Dimethyloctane, 4,4-Dimethyloctane, 3-Ethyl-3-methylheptane, 2-Methylnonane, 3-Methylnonane, 4-Methylnonane, tert-Butylcyclohexane, Butylcyclohexane, Isobutylcyclohexane, 4-Isopropyl-1-methylcyclohexane, Pentylcyclopentane, 1,1,3,5-Tetramethylcyclohexane, Cyclododecane, 1-Decene, 2-Decene, 3-Decene, 4-Decene, 5-Decene, 1,9-Decadiene, Decahydronaphthalene, 1-Decyne, 2-Decyne, 3-Decyne, 4-Decyne, 5-Decyne, 1,5,9-Decyne katriene, 2,6-dimethyl-2,4,6-octatriene, limonene, myrcene, 1,2,3,4,5-pentamethylcyclopentadiene, α-phellandrene, pinene, terpinene, tetrahydrodicyclopentadiene, 5,6-dihydrodicyclopentadiene, dicyclopentadiene, 1,4-decadiyne, 1,5-decadiyne, 1,9-decadiyne, 2,8-decadiyne, 4,6-decadiyne, n-undecane, amylcyclohexane, 1-undecene, 1,10-undecadiene, 1-undecyne, 3-undecyne, 5-undecyne, tricyclo[6.2.1.0, 2,7]Undec-4-ene, n-dodecane, 2-methylundecane, 3-methylundecane, 4-methylundecane, 5-methylundecane, 2,2,4,6,6-pentamethylheptane, 1,3-dimethyladamantane, 1-ethyladamantane, 1,5,9-cyclododecatriene, 1,2,4-trivinylcyclohexane, and aliphatic hydrocarbon solvents such as isoparaffin, cyclohexanone, cyclopentanone, 2-octanone, 2-nonanone, 2-heptanone, 3-heptanone, 4-heptanone, 2-hexanone, 3-hexanone, diisobutyl ketone , methylcyclohexanone, methyl n-pentyl ketone and other ketone-based solvents, 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol and other alcohol-based solvents, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol Examples of the solvent include ether solvents such as diethyl ether monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monopentyl ether, diethylene glycol monoheptyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, diisopropyl ether, diisobutyl ether, diisopentyl ether, di-n-pentyl ether, methylcyclopentyl ether, methylcyclohexyl ether, di-n-butyl ether, di-sec-butyl ether, di-sec-pentyl ether, di-tert-amyl ether, di-n-hexyl ether, and anisole; ester solvents such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate; lactone solvents such as γ-butyrolactone; and water.
[0216] The amount of the organic solvent added is preferably within a range of 10 to 50,000 parts by mass per 100 parts by mass of the combined resin of the polymer compound (A) and the resin component (D).
[0217] [Conductive powder (F)] In addition, the bioelectrode composition of the present invention can contain a conductive powder (F). Specific examples of the conductive powder (F) include carbon powder, metal powder, silicon powder, and / or lithium titanate powder.
[0218] [Metal powder] In order to enhance electronic conductivity, the bioelectrode composition of the present invention may contain a metal powder selected from gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium and indium. The amount of metal powder added is preferably within the range of 1 to 50 parts by mass per 100 parts by mass of the resin, which is the combined resin of the polymer compound (A) and the resin component (D).
[0219] As the type of metal powder, gold, silver and platinum are preferred from the viewpoint of electrical conductivity, and silver, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium and chromium are preferred from the viewpoint of cost. Noble metals are preferred from the viewpoint of biocompatibility. From these viewpoints in general, silver is the most preferred.
[0220] The shape of the metal powder can be spherical, disk-like, flake-like, or needle-like, but the addition of flake-like powder is preferred because it has the highest electrical conductivity. The metal powder should have a size of 100 μm or less and a tap density of 5 g / cm. 3 Below, the specific surface area is 0.5m 2 Flakes with a relatively low density and large specific surface area of 100 / g or more are preferred.
[0221] [Carbon powder] Carbon powder can be added as a conductivity enhancer. Examples of carbon powder (carbon material) include carbon black, graphite, carbon nanotubes, and carbon fibers. The carbon nanotubes may be either single-walled or multi-walled, and the surface may be modified with an organic group. The amount of the carbon material added is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin consisting of the polymer compound (A) and the resin component (D). The carbon powder is preferably either or both of carbon black and carbon nanotubes.
[0222] [Silicon powder] Silicon powder can be added as a conductivity improver. Examples of silicon powder include powders made of elemental silicon (Si), silicon monoxide (SiO), silicon carbide (SiC), silicon oxycarbide, silicate, and the like. Among them, silicon powders selected from Si, SiO, and SiC are preferred. The particle size of the powder is preferably smaller than 100 μm, more preferably 1 μm or less. The amount of silicon powder added is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin, which is the combined resin of the polymer compound (A) and the resin component (D).
[0223] [Lithium titanate powder] In order to increase the sensitivity of ion reception, lithium titanate powder can be added to the bioelectrode composition of the present invention. The lithium titanate powder can be Li2TiO3, LiTiO2, or Li4Ti5O with a spinel structure. 12 Examples of the powder include a powder containing a material represented by the molecular formula: and lithium titanate powder having a spinel structure is preferred. Lithium titanate particles composited with carbon can also be used. The particle size of the powder is preferably smaller than 100 μm, more preferably 1 μm or less. Since finer particles have a larger surface area, they can receive a larger number of ions, resulting in a highly sensitive bioelectrode. These may be composite powders with carbon. The amount of lithium titanate powder added is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin, which is the combined resin of the polymer compound (A) and the resin component (D).
[0224] Among these, it is preferable to further contain carbon powder, silver powder, and / or lithium titanate powder as the component (F).
[0225] [Tackifier] In addition, a tackifier may be added to the bioelectrode composition of the present invention in order to impart adhesion to a living body. Examples of such tackifiers include silicone resins, non-crosslinked siloxanes, non-crosslinked poly(meth)acrylates, and non-crosslinked polyethers.
[0226] [Crosslinking agent] An epoxy-based crosslinking agent can be added to the bioelectrode composition of the present invention. In this case, the crosslinking agent is a compound having a plurality of epoxy groups or oxetane groups in one molecule. The amount of the crosslinking agent to be added is 1 to 30 parts by mass per 100 parts by mass of the resin, which is the combined resin of the polymer compound (A) and the resin component (D).
[0227] [Crosslinking catalyst] A catalyst for crosslinking the epoxy group or oxetane group can also be added to the bioelectrode composition of the present invention. In this case, for example, the catalysts described in paragraphs 0027 to 0029 of JP-A-2019-503406 can be used. The amount of the catalyst added is 0.01 to 10 parts by mass per 100 parts by mass of the resin including the polymer compound (A) and the resin component (D).
[0228] [Ionic additives] The bioelectrode composition of the present invention can be added with an ionic additive to increase ionic conductivity. In consideration of biocompatibility, examples of the salts include sodium chloride, potassium chloride, calcium chloride, saccharin, acesulfame K, and the salts disclosed in JP-A-2018-44147, JP-A-2018-59050, JP-A-2018-59052, and JP-A-2018-130534.
[0229] As described above, the bioelectrode composition of the present invention is excellent in electrical conductivity and biocompatibility, lightweight, and can be manufactured at low cost, and can prevent a significant decrease in electrical conductivity even when wet or dried, can be applied to the skin to quickly collect signals, does not leave skin residue, and can form a transparent and highly designed bioelectrode biocontact layer. The bioelectrode biocontact layer formed using the bioelectrode composition of the present invention can exhibit excellent electrical conductivity, so that electrical signals from a living body, for example, the skin, can be efficiently transmitted to the device. In addition, this biocontact layer can exhibit excellent biocompatibility, so that allergies can be prevented even when worn on the skin for a long period of time. In addition, the electrical conductivity can be further improved by adding a conductivity enhancer such as a carbon material. In addition, by combining the bioelectrode composition of the present invention with a resin having adhesiveness and elasticity, a bioelectrode with particularly high adhesive strength and high elasticity can be manufactured. Furthermore, the bioelectrode composition of the present invention can improve its elasticity and adhesiveness to the skin by adding an additive or the like. In addition, the elasticity and adhesiveness can be adjusted by appropriately adjusting the composition of the polymer compound (A) of the bioelectrode composition of the present invention, the amount of the filler particles (B), and the thickness of the biocontact layer.
[0230] <Bioelectrode> The present invention also provides a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, the biocontact layer comprising a cured product of the bioelectrode composition of the present invention described above.
[0231] The bioelectrode of the present invention will be described in detail below with reference to the drawings, but the present invention is not limited thereto.
[0232] Fig. 1 is a schematic cross-sectional view showing an example of the bioelectrode of the present invention. The bioelectrode 1 in Fig. 1 has a conductive substrate 2 and a biocontact layer 3 formed on the conductive substrate 2. The biocontact layer 3 is a layer in which an ionic polymer (polymer compound (A)) 5 and filler particles 4 are dispersed in a resin 6. The ionic polymer 5 is an example of the polymer compound (A) described above. The resin 6 is the compound (C) having a polyglycerin structure and a resin component (D) described above. The biocontact layer 3 is a cured product of a bioelectrode composition of an example of the present invention.
[0233] When using such a bioelectrode 1 of FIG. 1, as shown in FIG. 2, the biocontact layer 3 (i.e., a layer in which an ionic polymer 5 and filler particles 4 are dispersed in a resin 6) is brought into contact with a living body 7, and an electrical signal is taken from the living body 7 by the ionic polymer 5 and the filler particles 4, and the electrical signal is conducted to a sensor device or the like (not shown) via the conductive substrate 2. In this way, the bioelectrode of the present invention can achieve both electrical conductivity and biocompatibility by the above-mentioned ionic polymer (ionic material), and has adhesiveness, so that the contact area with the skin is constant, and electrical signals from the skin can be obtained stably and with high sensitivity. In particular, as described above, the bioelectrode composition of the present invention can form a biocontact layer that can be attached to the skin and quickly collect signals. Therefore, the bioelectrode 1 of FIG. 1 can be attached to the living body 7 and quickly collect signals.
[0234] Each of the constituent materials of the bioelectrode of the present invention will be described in more detail below.
[0235] [Conductive base material] The bioelectrode of the present invention has a conductive substrate. This conductive substrate is usually electrically connected to a sensor device or the like, and conducts an electrical signal extracted from a living body via a living body contact layer to the sensor device or the like.
[0236] The conductive substrate is not particularly limited as long as it is conductive, but it is preferable that the conductive substrate contains at least one metal selected from the group consisting of gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, and carbon.
[0237] The conductive substrate is not particularly limited, and may be a hard conductive substrate, a flexible conductive film, a substrate in which a conductive paste is coated on an elastic film, a cloth coated with a conductive paste, or a cloth in which a conductive polymer is kneaded. The conductive substrate may be flat or uneven, or may be a mesh woven from metal wires, and may be appropriately selected according to the application of the bioelectrode. Among these, considering that the substrate is attached to the skin, a substrate in which a conductive paste is coated on an elastic film or a cloth is preferred. Examples of the elastic film include polyurethane and polyester. As the conductive paste, a conductive powder such as carbon, silver, gold, or copper is mixed with a solvent in an elastic resin such as polyurethane, polyester, silicone, or nitrile resin is used.
[0238] [Bio-contact layer] The bioelectrode of the present invention has a biocontact layer formed on a conductive substrate. This biocontact layer is the part that actually comes into contact with the living body when the bioelectrode is used, and has electrical conductivity and adhesiveness. The biocontact layer is a cured product of the bioelectrode composition of the present invention described above, that is, an adhesive resin layer containing the above-mentioned polymer compound (A) (ionic material (salt)) and one or more filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles, as well as an optional compound having a polyglycerin structure (C), and additives such as a resin component (D).
[0239] The adhesive strength of the living body contact layer is preferably in the range of 0.5 N / 25 mm or more and 20 N / 25 mm or less. The adhesive strength is generally measured by the method shown in JIS Z 0237. Although a metal substrate such as SUS (stainless steel) or a PET (polyethylene terephthalate) substrate can be used as the substrate, human skin can also be used for measurement. The surface energy of human skin is lower than that of metals and various plastics, and is close to that of Teflon (registered trademark). Therefore, human skin has a low adhesive property.
[0240] The thickness of the biocontact layer of the bioelectrode is preferably 1 μm to 5 mm, more preferably 2 μm to 3 mm. The thinner the biocontact layer, the weaker the adhesive strength, but the more flexible it is, the lighter it is, and the better it fits to the skin. The thickness of the biocontact layer can be selected based on the balance between adhesiveness and texture on the skin.
[0241] The bioelectrode of the present invention preferably has a biocontact layer that has been humidified. A bioelectrode including such a biocontact layer can collect signals more quickly when attached to the skin.
[0242] In addition, in the bioelectrode of the present invention, similar to conventional bioelectrodes (for example, the bioelectrode described in JP 2004-033468 A), a separate adhesive film may be provided on the biocontact layer to prevent the bioelectrode from peeling off from the living body during use. When providing a separate adhesive film, it is sufficient to form the adhesive film using an adhesive film material such as an acrylic type, a urethane type, or a silicone type. In particular, the silicone type has high oxygen permeability, so that the skin can breathe while it is attached, and has high water repellency, so that the adhesiveness is less likely to decrease due to sweat, and further, is less irritating to the skin, so it is preferable. In addition, in the bioelectrode of the present invention, as described above, peeling off from the living body can be prevented by adding an adhesive imparting agent to the bioelectrode composition or using a resin that has good adhesiveness to the living body, so that the above-mentioned separate adhesive film is not necessarily required.
[0243] When the bioelectrode of the present invention is used as a wearable device, the wiring between the bioelectrode and the sensor device and other components are not particularly limited, and for example, those described in JP 2004-033468 A can be applied.
[0244] As described above, the bioelectrode of the present invention includes a biocontact layer formed of the cured product of the bioelectrode composition of the present invention, and therefore has excellent electrical conductivity and biocompatibility, is lightweight, can be manufactured at low cost, can prevent a significant decrease in electrical conductivity even when wet or dried, can be attached to the skin to quickly collect signals, does not leave skin residue, and can be a transparent and highly designed bioelectrode. The biocontact layer of the bioelectrode of the present invention can exhibit excellent electrical conductivity, so that electrical signals from a living body, for example, the skin, can be efficiently transmitted to a device. In addition, this biocontact layer can exhibit excellent biocompatibility, so that allergies can be prevented even when worn on the skin for a long period of time. In addition, the electrical conductivity of the biocontact layer of the bioelectrode of the present invention can be further improved by adding metal powder. In addition, a bioelectrode with particularly high adhesive strength and high elasticity can be manufactured by combining the bioelectrode composition of the present invention with a resin having adhesiveness and elasticity. Furthermore, by adding an additive or the like to the biocontact layer, the elasticity and adhesiveness of the biocontact layer to the skin can be improved. In addition, the stretchability and adhesiveness can be adjusted by appropriately adjusting the composition of the polymer compound (A) and / or the compound (C) having a polyglycerin structure in the bioelectrode composition of the present invention, the amount of one or more filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles, and the thickness of the biocontact layer. Therefore, such a bioelectrode of the present invention is particularly suitable as a bioelectrode used in a medical wearable device.
[0245] <Manufacturing method of bioelectrodes> The present invention provides a method for manufacturing a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, characterized in that the bioelectrode composition described above is applied to the conductive substrate and cured to form the biocontact layer.
[0246] The conductive substrate, the bioelectrode composition, and the like used in the method for producing the bioelectrode of the present invention may be the same as those described above.
[0247] The method for applying the bioelectrode composition onto the conductive substrate is not particularly limited, but suitable methods include, for example, dip coating, spray coating, spin coating, roll coating, flow coating, doctor coating, screen printing, flexographic printing, gravure printing, stencil printing, and inkjet printing.
[0248] The resin curing method is not particularly limited and may be appropriately selected depending on the type of compound (C) having a polyglycerin structure and resin (D) used in the bioelectrode composition, but it is preferable to cure the composition by, for example, heat or light, or both. In addition, a catalyst that generates an acid or base may be added to the bioelectrode composition to cause a crosslinking reaction and cure the composition.
[0249] The temperature for heating is not particularly limited and may be appropriately selected depending on the type of compound (C) having a polyglycerin structure and resin (D) used in the bioelectrode composition, but is preferably about 50 to 250°C.
[0250] In addition, when heating and light irradiation are combined, heating and light irradiation may be performed simultaneously, or heating may be performed after light irradiation, or light irradiation may be performed after heating. In addition, air drying may be performed before heating after coating in order to evaporate the solvent.
[0251] The hardened film, i.e., the formed biocontact layer, can be immersed in water, its surface wiped with absorbent cotton, gauze, or nonwoven fabric, or its surface can be moistened with water droplets, or sprayed with water vapor or mist, improving its compatibility with the skin and enabling biosignals to be obtained quickly. Water mixed with alcohol can also be used to reduce the size of the water vapor or mist droplets.
[0252] Before attaching the bioelectrode of the present invention to the skin, the skin can be wiped with gauze, absorbent cotton, nonwoven fabric, etc. containing water or alcohol to remove oils and grease from the skin and moisten the skin, thereby improving the sensitivity of the biosignal. If the skin is dry, ions will not be released from the skin. Moistening the skin and the bioelectrode promotes the release of ions from the skin, improving the sensitivity of the biosignal. It is preferable to soak the absorbent cotton, nonwoven fabric, gauze, etc. in water or water-soluble alcohols such as ethanol, glycerin, ethylene glycol, and diethylene glycol that contain water.
[0253] As described above, the manufacturing method of the bioelectrode of the present invention makes it possible to easily manufacture, at low cost, the bioelectrode of the present invention which has excellent conductivity and biocompatibility, is lightweight, and can prevent a significant decrease in conductivity whether it is wet or dry, can be attached to the skin to quickly collect signals, does not leave any residue on the skin, and is transparent and has a highly designable appearance. EXAMPLES
[0254] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these. In the following, "Me" represents a methyl group and "Vi" represents a vinyl group.
[0255] [High molecular compound (A)] Ionic polymers 1 to 19, which were blended as polymer compound (A) (ionic material (conductive material)) in the bioelectrode composition solution of the examples, and comparative ionic polymer 1, which was blended in the bioelectrode composition solution of the comparative example, were synthesized as follows. A 30% by mass cyclopentanone solution of each monomer was placed in a reaction vessel and mixed, and the reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassed under reduced pressure and nitrogen blowing were repeated three times. After heating to room temperature, 0.01 mol of azobisisobutyronitrile (AIBN) was added as a polymerization initiator relative to 1 mol of the total monomers, and the mixture was heated to 60°C and reacted for 15 hours. After drying the solvent, the composition of the obtained polymer was as follows: 1 The molecular weight (Mw) and dispersity (Mw / Mn) of the obtained polymer were confirmed by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent. The ionic polymers 1 to 19 and comparative ionic polymer 1 thus synthesized are shown below.
[0256] Ionic Polymer 1 Mw=38,100 Mw / Mn=1.91 [ka] (The number of repetitions in the formula indicates the average value.)
[0257] Ionic Polymer 2 Mw=36,100 Mw / Mn=1.93 [ka] (The number of repetitions in the formula indicates the average value.)
[0258] Ionic Polymer 3 Mw=150,600 Mw / Mn=1.85 [ka]
[0259] Ionic Polymer 4 Mw=44,400 Mw / Mn=1.94 [ka] (The number of repetitions in the formula indicates the average value.)
[0260] Ionic Polymer 5 Mw=43,100 Mw / Mn=1.88 [ka] (The number of repetitions in the formula indicates the average value.)
[0261] Ionic Polymer 6 Mw=41,200 Mw / Mn=1.72 [ka] (The number of repetitions in the formula indicates the average value.)
[0262] Ionic Polymer 7 Mw=43,600 Mw / Mn=1.93 [ka]
[0263] Ionic Polymer 8 Mw=31,600 Mw / Mn=2.10 [ka] (The number of repetitions in the formula indicates the average value.)
[0264] Ionic Polymer 9 Mw=55,100 Mw / Mn=2.02 [ka] (The number of repetitions in the formula indicates the average value.)
[0265] Ionic Polymer 10 Mw=87,500 Mw / Mn=2.01 [ka] (The number of repetitions in the formula indicates the average value.)
[0266] Ionic Polymer 11 Mw=43,600 Mw / Mn=1.91 [ka] (The number of repetitions in the formula indicates the average value.)
[0267] Ionic Polymer 12 Mw=97,100 Mw / Mn=2.20 [ka] (The number of repetitions in the formula indicates the average value.)
[0268] Ionic Polymer 13 Mw=98,300 Mw / Mn=2.05 [ka] (The number of repetitions in the formula indicates the average value.)
[0269] Ionic Polymer 14 Mw=68,900 Mw / Mn=2.26 [ka]
[0270] Ionic Polymer 15 Mw=67,100 Mw / Mn=1.89 [ka]
[0271] Ionic Polymer 16 Mw=23,400 Mw / Mn=1.77 [ka]
[0272] Ionic Polymer 17 Mw=34,300 Mw / Mn=1.75 [ka] (The number of repetitions in the formula indicates the average value.)
[0273] Ionic Polymer 18 Mw=37,700 Mw / Mn=1.79 [ka] (The number of repetitions in the formula indicates the average value.)
[0274] Ionic Polymer 19 Mw=46,300 Mw / Mn=2.21 [ka] (The number of repetitions in the formula indicates the average value.)
[0275] Comparative ionic polymer 1 Mw=46,700 Mw / Mn=2.25 [ka]
[0276] [Filler particles (B)] The filler particles (B) blended in the bioelectrode composition solutions of the Examples and Comparative Examples are shown below. Sigma-Aldrich fumed silica, average particle size 0.007μm Sigma-Aldrich Aluminum Oxide Average particle size less than 0.050μm Titanium oxide manufactured by Sigma-Aldrich, average particle size less than 0.025 μm Sigma-Aldrich Zirconium oxide, average particle size less than 0.100μm Nippon Aerosil Co., Ltd. Aerosil 200 Average particle size 0.012 μm Nippon Aerosil Co., Ltd. Aerosil RX200 Average particle size 0.012μm Nippon Aerosil Co., Ltd. Aerosil RX300 Average particle size 0.007μm Nippon Aerosil Co., Ltd. Aerosil RY300 Average particle size 0.007μm
[0277] [Compounds (C) having a polyglycerol structure] The polyglycerin silicone compounds 1 to 22 and polyether silicone compound 1 that were blended as the compound (C) having a polyglycerin structure in the bioelectrode composition solution of the embodiment are shown below. These compounds were synthesized by hydrosilylation reaction of a silicone compound having a SiH group, a polyglycerin compound having a double bond, an alkylene group compound, and a polyether compound having a double bond, in the presence of a platinum catalyst, as described in JP 2019-99469 A.
[0278] [ka]
[0279] [ka]
[0280] [ka]
[0281] [ka]
[0282] [ka]
[0283] [Resin component (D)] Siloxane compounds 1 to 4 that were blended as silicone resins in the bioelectrode composition solutions of the Examples and Comparative Examples are shown below. (Siloxane Compound 1) The viscosity of a 30% toluene solution was 27,000 mPa·s, the alkenyl group content was 0.007 mol / 100 g, and the vinyl group-containing polydimethylsiloxane whose molecular chain ends were blocked with SiMe2Vi groups was designated as siloxane compound 1. (Siloxane Compound 2) Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A 60% toluene solution of siloxane compound 2 (SiO2 unit / SiO2 unit = 0.8) was used as siloxane compound 2. (Siloxane Compound 3) 40 parts by mass of vinyl-containing polydimethylsiloxane whose molecular chain ends are capped with OH, whose viscosity in a 30% toluene solution is 42,000 mPa s and whose alkenyl group content is 0.007 mol / 100 g, Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A solution consisting of 100 parts by mass of a 60% toluene solution of 1,2-dichlorophenyl ether (SiO2 unit / SiO2 unit=0.8) and 26.7 parts by mass of toluene was heated under reflux for 4 hours and then cooled to obtain siloxane compound 3 in which polydimethylsiloxane was bonded to the MQ resin. (Siloxane Compound 4) As the methyl hydrogen silicone oil, KF-99 manufactured by Shin-Etsu Chemical Co., Ltd. was used.
[0284] The acrylic polymers blended as the acrylic resin in the bioelectrode composition solution are shown below. Acrylic Polymer 1 Mw=108,000 Mw / Mn=2.32 [ka] (The number of repetitions in the formula indicates the average value.)
[0285] Silicone pendant urethane (meth)acrylates 1 to 3 and urethane (meth)acrylate 4 blended as silicone, acrylic, or urethane resins in the bioelectrode composition solutions of the Examples and Comparative Examples are shown below.
[0286] [ka] (The number of repetitions in the formula indicates the average value.)
[0287] [Crosslinking agent] The crosslinking agents blended in the bioelectrode composition solutions of the Examples and Comparative Examples are shown below. [ka]
[0288] [Organic solvent (E)] The organic solvents (E) blended in the bioelectrode composition solutions of the Examples and Comparative Examples are shown below. EDE: Diethylene glycol diethyl ether BE: Diethylene glycol butyl ether Isopar G (ExxonMobil): Isoparaffin
[0289] [others] The lithium titanate powder, silver flakes, radical generator, platinum catalyst, and conductivity enhancer (carbon black, multi-walled carbon nanotubes) blended as additives in the bioelectrode composition solutions of the examples and comparative examples are shown below. Lithium titanate powder (spinel): Sigma-Aldrich, size 200 nm or less Silver flakes: Sigma-Aldrich, average size 10 μm Radical generator: BASF Irgacure TPO Platinum catalyst: CAT-PL-56 manufactured by Shin-Etsu Chemical Co., Ltd. Carbon black: Denka Black Li-400 manufactured by Denka Multi-walled carbon nanotubes: Sigma-Aldrich, diameter 110-170 nm, length 5-9 μm
[0290] [Examples 1 to 42, Comparative Examples 1 to 2] Ionic materials (salts), filler particles, polyglycerin silicone compounds, resins, organic solvents, additives (radical generators, platinum catalysts, conductivity enhancers, lithium titanate powder, ionic additives, platinum control agents, etc.), and crosslinkers were blended in the compositions shown in Tables 1 to 5 to prepare bioelectrode composition solutions (bioelectrode composition solutions 1 to 42, comparative bioelectrode composition solutions 1 to 2).
[0291] [Table 1]
[0292] [Table 2]
[0293] [Table 3]
[0294] [Table 4]
[0295] [Table 5]
[0296] (Preparation of samples for biosignal evaluation) A conductive paste, Dotite FA-333, manufactured by Fujikura Kasei, was coated on a thermoplastic urethane (TPU) film ST-604 manufactured by Bemis by screen printing, and the coating film was baked in an oven at 120°C for 10 minutes to print a keyhole-shaped conductive pattern including a circular part with a diameter of 2 cm and a rectangular part. A bioelectrode composition solution shown in Tables 1 to 5 was applied by screen printing on top of the circular part of the printed conductive pattern, and the coating film was air-dried at room temperature for 10 minutes, and then baked in an oven at 125°C for 10 minutes to evaporate the solvent and harden it. In Examples 10 to 17, a xenon lamp was further used in a nitrogen atmosphere at 200 mJ / cm. 2 The bioelectrode compositions were cured by irradiation with a radiation exposure amount of 1000 nm to obtain a biocontact layer, which was a cured product of each bioelectrode composition (Bioelectrodes 1 to 42, Comparative Bioelectrodes 1 to 2).
[0297] Fig. 3 is a schematic diagram of the bioelectrode produced in the example after printing. As shown in Fig. 3, a plurality of bioelectrodes 1 were produced on a thermoplastic urethane film 20. Each bioelectrode 1 included a keyhole-shaped conductive pattern 2 as a conductive substrate and a biocontact layer 3 formed on the circular portion of the conductive pattern 2.
[0298] Next, as shown in FIG. 4, the thermoplastic urethane film 20 on which the bioelectrode 1 was printed was cut out and double-sided tape 21 was attached to it to prepare three bioelectrode samples 10 (samples for evaluating biosignals) for each composition solution.
[0299] (Measurement of the thickness of the biological contact layer) The thickness of the biocontact layer of each of the bioelectrode samples prepared as described above was measured using a micrometer. The results are shown in Table 6.
[0300] (Biological signal measurement) The conductive wiring pattern made of conductive paste of the bioelectrode was connected to a portable electrocardiograph HCG-901 manufactured by Omron Healthcare Co., Ltd. with a conductive wire, and the positive electrode of the electrocardiograph was attached to the LA position of the human body in Figure 5, the negative electrode to the LL position, and the earth to the RA position. Immediately after attachment, electrocardiogram measurement was started, and the time until the electrocardiogram waveform consisting of P, Q, R, S, and T waves shown in Figure 6 appeared was measured. The results are shown in Table 6. Also, immediately before attachment, the electrode surface or skin may be wiped with gauze impregnated with a solution containing 70% ethanol and 30% water.
[0301] (Observation of remaining skin) After measuring the electrocardiogram waveform, the electrodes were left on the skin, and after one hour, the electrodes were removed from the skin and the area remaining on the skin was observed. The results are shown in Table 6.
[0302] [Table 6]
[0303] As shown in Table 6, in Examples 1 to 30 and Examples 40 to 42 in which a biocontact layer was formed using the bioelectrode composition of the present invention, which contains the polymer compound (A) (salt (ionic material)) having a specific structure described above, one or more filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles, and a compound (C) having a polyglycerin structure, it was possible to obtain a biosignal (ECG signal) immediately after application to the body, and no skin residue was left behind. In addition, in Examples 31 to 38 in which a biocontact layer was formed using the bioelectrode composition of the present invention, which contains the polymer compound (A) (salt (ionic material)) having a specific structure, and one or more filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles, it took a little time to obtain a biosignal (ECG signal) after application to the body, but no skin residue was left behind. The biocontact layer of Example 39 contained the polymer compound (A), filler particles (B), and a compound having a polyether structure. As a result, the time to obtain a biosignal was slightly shortened by adding the compound having a polyether structure, but the effect was not as great as that of adding the compound having a polyglycerin structure (C). From this, it can be seen that although both the polyether structure and the polyglycerin structure have hydrophilicity, polyglycerin having a hydroxyl group is more effective in this system. On the other hand, the biocontact layer of Comparative Example 1 contained the polymer compound (A) and the compound having a polyglycerin structure (C) but did not contain the filler particles (B). As a result, the time to obtain a biosignal was short for the biocontact layer of Comparative Example 1, but skin residue occurred when peeled off from the skin. This is thought to be because the affinity between the polymer compound (A) and the compound having a polyglycerin structure (C) and carbon black is poor because it does not contain the filler particles (B). In addition, the biocontact layer of Comparative Example 2 contained the filler particles (B) but did not contain the polymer compound (A). As a result, it is thought that the biocontact layer of Comparative Example 2 did not exhibit sufficient ion sensitivity, and the time to obtain a biosignal was long.
[0304] From the above, it has become clear that a bioelectrode having a biocontact layer formed using the bioelectrode composition of the present invention can quickly obtain a biosignal. That is, the bioelectrode composition of the present invention can provide a bioelectrode that can quickly obtain a biosignal when attached to a living body and does not remain on the skin, by using the above-described polymer compound (A) and one or more filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles.
[0305] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0306] 1...bioelectrode, 2...conductive substrate (conductive pattern), 3...biocontact layer, 4...filler particles, 5...ionic polymer (polymer compound (A)), 6...resin, 7...Body, 10...Bioelectrode sample, 20...Thermoplastic urethane film, 21...Double-sided tape.
Claims
1. A polymer compound (A) containing a repeating unit a having a structure selected from the group consisting of an ammonium salt, a sodium salt, a potassium salt, and a silver salt of any one of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide; one or more types of filler particles (B) selected from silica particles, alumina particles, titania particles, and zirconia particles; Furthermore, a compound (C) having a polyglycerol structure and The compound (C) having a polyglycerin structure is a silicone compound having a polyglycerin structure, and the silicone compound having a polyglycerin structure is represented by either of the following general formulas (4) and (5). 【Chemistry 1】 (In the formula, R 1 's are each independent and may be the same or different from each other, and are a hydrogen atom, a linear or branched alkyl group having 1 to 50 carbon atoms, or a phenyl group, and may contain an ether group or may be a silicone chain represented by general formula (6); R 2 's are a group having a polyglycerin group structure represented by general formula (4)-1 or general formula (4)-2; R 3 's are each independent and may be the same or different from each other, and are the R 1 ' group or the R 2 ' group; R 4 's are each independent and may be the same or different from each other, and are the R 1 ' group, the R 2 ' group, or an oxygen atom. When R 4 ' is an oxygen atom, two R 4 The R 3 ' groups may be bonded to form a single ether group to form a ring together with the silicon atom. a' may be the same or different and is 0 to 100, b' is 0 to 100, and a'+b' is 0 to 200. However, when b' is 0, at least one of R 3 ' is the above-mentioned R 2 ' group. R 5 ' is an alkylene group having 2 to 10 carbon atoms or an aralkylene group having 7 to 10 carbon atoms, R 6 ' and R 7 ' are alkylene groups having 2 to 6 carbon atoms, R 7 ' may be an ether group, c' is 0 to 20, and d' is 1 to 20.)
2. The bioelectrode composition according to claim 1, characterized in that the repeating unit a has a structure represented by any one of the following general formulas (1)-1 to (1)-4. 【Chemistry 2】 (In general formula (1)-1, Rf 1 and Rf 2 is a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group, and Rf 1 and Rf 2 When Rf is an oxygen atom, 1 and Rf 2 is an oxygen atom bonded to a carbon atom to form a carbonyl group, and Rf 3 and Rf 4 is a hydrogen atom, a fluorine atom, or a trifluoromethyl group, and Rf 1 ~Rf 4 At least one of Rf is a fluorine atom or a trifluoromethyl group. 5 , Rf 6 and Rf 7 Each of M is a fluorine atom or a linear or branched alkyl group having 1 to 4 carbon atoms and has at least one fluorine atom. + is an ion selected from an ammonium ion, a sodium ion, a potassium ion, and a silver ion. In the general formula (1)-2, m is an integer of 1 to 4.
3. The bioelectrode composition according to claim 1 or 2, characterized in that the repeating unit a has one or more types selected from repeating units a1 to a7 represented by the following general formula (2). 【Chemistry 3】 (In general formula (2), R 1 , R 3 , R 5 , R 8 , R 10 , R 11 , and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 , and R 14 are each independently a single bond or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms. The hydrocarbon group may have an ester group, an ether group, or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms; R 7 One or two of the hydrogen atoms in X may be substituted with a fluorine atom. 1 , X 2 , X 3 , X 4 , X 6 , and X 7 each independently represents a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group; X 5 is a single bond, an ether group, or an ester group. Y is an oxygen atom or -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 Rf may form a ring together with 1 ' and Rf 5 M' is a fluorine atom, a trifluoromethyl group, or a linear or branched alkyl group having 1 to 4 carbon atoms, and has at least one fluorine atom. m is an integer from 1 to 4. a1, a2, a3, a4, a5, a6, and a7 are within the ranges of 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0<a1+a2+a3+a4+a5+a6+a7≦1.
0. + is an ion selected from ammonium ion, sodium ion, potassium ion, and silver ion.
4. The bioelectrode composition according to any one of claims 1 to 3, characterized in that the polymer compound (A) contains an ammonium ion represented by the following general formula (3) as an ammonium ion constituting the ammonium salt: 【Chemistry 4】 (In general formula (3), R 101d , R 101e , R 101f and R 101g R each represents a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 14 carbon atoms, a linear, branched, or cyclic alkenyl group or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more groups selected from an ether group, a carbonyl group, an ester group, a hydroxy group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d and R 101e , or R 101d , R 101e and R 101f may form a ring together with the nitrogen atom to which they are attached, and when they form a ring, R 101d and R 101e , or R 101d , R 101e and R 101f is an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having the nitrogen atom in the general formula (3) in the ring.
5. The bioelectrode composition according to any one of claims 1 to 4, further comprising a resin component (D) which is at least one selected from the group consisting of silicone-based resins, acrylic-based resins, and urethane-based resins.
6. The resin component (D) is R x SiO (4-x)/2 units (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5) and SiO 2 6. The bioelectrode composition according to claim 5, which contains any one of a silicone resin having a unit, a diorganosiloxane having an alkenyl group, and an organohydrogenpolysiloxane having a SiH group.
7. The bioelectrode composition according to any one of claims 1 to 6, further comprising an organic solvent (E).
8. 8. The bioelectrode composition according to claim 1, further comprising carbon powder, silver powder, silicon powder, and / or lithium titanate powder as component (F).
9. 9. The bioelectrode composition according to claim 8, wherein the carbon powder is either or both of carbon black and carbon nanotubes.
10. A conductive substrate; A living body contact layer formed on the conductive substrate; A bioelectrode having A bioelectrode, characterized in that the biocontact layer comprises a cured product of the bioelectrode composition according to any one of claims 1 to 9.
11. The bioelectrode according to claim 10, characterized in that the conductive base material contains one or more selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, and carbon.
12. 12. The bioelectrode according to claim 10, wherein the biological contact layer is subjected to a humidification treatment.
13. A method for producing a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, comprising the steps of: The bioelectrode composition according to any one of claims 1 to 9 is applied onto the conductive substrate, and cured to form the biocontact layer. A method for manufacturing a bioelectrode comprising the steps of:
14. The method for manufacturing a bioelectrode according to claim 13, characterized in that the conductive base material contains one or more selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, and carbon.
15. 15. The method for producing a bioelectrode according to claim 13, further comprising the steps of: immersing the biocontact layer in water or subjecting the biocontact layer to a humidifying treatment after the biocontact layer is formed.
Citation Information
Patent Citations
Flexible microelectrode array of stimulus response
CN207091329U
Conductive millable urethane rubber electrode
JP1993095924A
Floor slip prevention agent and method for preventing floor slip using the same
JP2001098253A
Silicone rubber composition for living body electrode and electrode for living body
JP2003225217A
Lithium ion conductive composite
JP2007059092A